Psychometric properties of the Brazilian version of Clinical Perfectionism Questionnaire after rewording negatively keyed items - Rocha,Luiz Fellipe Dias da (2022)
Abstract The present study aims to verify the psychometric properties of the Brazilian version of Clinical Perfectionism Questionnaire after rewording negatively keyed items into positive (CPQ+). It was used a convenience sample of 168 Brazilian university students (M=25.37, SD=7.40), being 76.8% women. After rewording the negatively keyed items into positive, the CPQ+ was applied. The Depression, Anxiety and Stress Scales - Short Form (DASS-21) were also applied. The Corrected Item-Total Correlation values of CPQ+ items were close to or higher than the cutoff point. After exclusion of item 8, due to crossloading, and correlation between errors of items 3 and 10, the correlated two-factor model presented the best fit of latent structure to CPQ+, through Confirmatory Factor Analysis. The Perfectionistic Concerns dimension of CPQ+ was greater related to global score of DASS-21 in comparison to the Perfectionistic Striving dimension, indicating good validity regarding other variables. In summary, results recommend the use of CPQ+ presented in this study, it is, a version with 11 positive items.